2013
DOI: 10.1128/aac.02011-12
|View full text |Cite
|
Sign up to set email alerts
|

Blood, Tissue, and Intracellular Concentrations of Azithromycin during and after End of Therapy

Abstract: cAlthough azithromycin is extensively used in the treatment of respiratory tract infections as well as skin and skin-related infections, pharmacokinetics of azithromycin in extracellular space fluid of soft tissues, i.e., one of its therapeutic target sites, are not yet fully elucidated. In this study, azithromycin concentration-time profiles in extracellular space of muscle and subcutaneous adipose tissue, but also in plasma and white blood cells, were determined at days 1 and 3 of treatment as well as 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
95
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 56 publications
5
95
0
5
Order By: Relevance
“…After AZM is distributed to the acidic compartment in the cell, it is protonated and thus becomes trapped in the cell. This ion-trapping mechanism is responsible for the long retention of AZM in tissues and the very slow release of AZM from intracellular compartments, which are characteristics consistent with its large distribution volume and long half-life (4,8,9).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…After AZM is distributed to the acidic compartment in the cell, it is protonated and thus becomes trapped in the cell. This ion-trapping mechanism is responsible for the long retention of AZM in tissues and the very slow release of AZM from intracellular compartments, which are characteristics consistent with its large distribution volume and long half-life (4,8,9).…”
mentioning
confidence: 78%
“…The interstitial fluid (ISF), i.e., the extracellular tissue space, is the primary site of most bacterial infections (8,10). However, most studies have focused on the AZM concentration in WBCs, different tissue-specific phagocytes (i.e., the intracellular tissue space), and tissue homogenates (8,(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considered collectively, the findings of these preclinical studies indicate that azithromycin is a weak hERG blocker and even under conditions where it has been seen to delay repolarization, it did not share proarrhythmic features with other macrolides. In healthy volunteers receiving short-term azithromycin (500 mg daily for 3 days), peak plasma levels close to 400 ng/ml ($0.5 mM) have been reported [Matzneller et al 2013] that are $2000-fold less than the estimated hERG IC 50 of >1000 mM [Thomsen et al 2006]. Although it has been reported that tissue concentrations of azithromycin can significantly exceed those in plasma (with muscle concentrations of $1 mg/kg, in excess of 1 mM), it is not clear that these are indicative of possible cardiac levels commensurate with significant hERG block [Foulds et al 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, azithromycin levels accumulated somewhat following multiple administrations not only in the conjunctiva but also in soft tissues such as muscle and subcutaneous adipose tissue. 22,27) Therefore, we cannot exclude the possibility that azithromycin might eventually reach meaningful concentrations in the meibomian glands. It is important, however, to recognize the limited penetration of azithromycin into the meibomian glands.…”
Section: Discussionmentioning
confidence: 99%